Python Programming : Using Problem Solving Approach - Reema Thareja (New Delhi Oxford University Press, 2017)
Python Programming is designed as a textbook to fulfil the requirements of the first-level course in Python programming. It is suited for undergraduate degree students of computer science engineering, information technology as well as computer applications. This book will enable students to apply the Python programming concepts in solving real-world problems. The book begins with an introduction to computers, problem solving approaches, programming languages, object oriented programming, and Python programming. Separate chapters dealing with the important constructs of Python language such as control statements, functions, strings, files, data structures, classes and objects, inheritance, operator overloading, and exceptions are provided in the book.
Keywords: Python Programming; Python strings Revisited